Borneo Manga Cafe / Arviana Modolpop... [et al.] - Annuar, Khairul Kaspul; Jamuri, Sherlliecadelora Veronella; Murphy, Nadia; Isyam, Mohd Faiznor; Salim, Muhd Safian; Modolpop, Arviana (2016)
"EVERY SPACE IS MEANINGFUL, YOUR PRIORITY IS OUR DESIRE" is Borneo Manga cafe's tagline. Borneo Manga Cafe (BMC) is service type of business founded as of 17111 December 2016 to be ONE of the leading BUMIPUTRA conceptual cafe management in Malaysia and in the region also providing efficient and effective services to our customers. Despite many conceptual cafe in Malaysia, ours inspired by the Manga or Anime a Japanese animation characters and stories. Borneo Manga Cafe provides latest Manga for the "otaku" or anime lover and others to read for free while enjoying our delicious signature dishes and beverages which is "Poprasik" and mocktails with affordable low prices and more importantly served halal. Other than that, we also entertain them with karaoke and busking on weekend's night which is on Sunday, 8 pm - 11 pm and Saturday 8 pm - 11 pm respectively. Borneo Manga Cafe expected that in the future this cafe will be one of Kota Kinabalu main attraction to tourists and local citizen and will be visited often because we plan to celebrate Malaysian's festive seasons with mixed theme concept of anime. Our target market includes tourist and teenagers. The total addressable market is RM 4, 800,000. Borneo Manga cafe is pre-revenue but is gaining meaningful traction with customer. Based on this plan, Borneo Manga Cafe projects that it will be able to capture at least 46% of this market over the next 2 years. Our competition comprised of Nunpat, Hardrock cafe, and Starbucks. Borneo Manga Cafe competitive advantages lies in it freshness, uniqueness of the concept and much more cheaper prices of products.